A facile and clean process for exfoliating MoS2 nanosheets assisted by a surface active agent in aqueous solution. (15th August 2018) - Guan, Zhishu; Wang, Chao; Li, Wenjie; Luo, Suibin; Yao, Yingbang; Yu, Shuhui; Sun, Rong; Wong, Ching-Ping
Abstract: A facile, efficient and environmentally friendly process to exfoliate MoS2 is essentially critical to apply the obtained mono- and few-layer nanosheets in various electronic devices and sensors. Here we report a liquid phase exfoliation method for exfoliation of MoS2, which employs a surfactant of sodium dodecyl benzene sulfonate (SDBS) in water. The nonpolar benzene rings in SDBS can firmly bind to the MoS2 layer, facilitating the effective exfoliation of nanosheets in aqueous solution. It is found that the exfoliation efficiency and thickness of MoS2 nanosheets are related to the concentration of SDBS, and the mechanism was investigated. Defect free mono- and few-layer MoS2 nanosheets are obtained by controlling the amount of SDBS in solution, which exhibit stable dispersion in water over months, and it renders them as having great potential for solution-based device fabrication.